Борьба двух стихий - Кораблев, О.Л. (My University, 2013)
Modern education should be designed on the basis of current scientific knowledge about the person. The theory of environmental approach YS Manuylova takes into account in the formation of the category probabilities. Element is the human element of the environment that characterizes the probability of opportunities available in the environment. Generating the elements necessary to support the development and the generation of the elements necessary to support the processes of formation – they are different elements that contribute to the formation of different types of personalities.